Failure prediction of marine non-planar composite π joints based on combined 2D material model and progressive damage method. (15th February 2021) - Zhang, Yongxiang; Jiang, Linfei; Gong, Yu; Liu, Hao; Zhao, Jian; Ren, Sue
Abstract: Non-planar composite π joints are receiving increasing attention in marine engineering. Efficient two-dimensional (2D) finite element (FE) methods, which can accurately predicted the failure behavior of this kind of joint, are critically meaningful for structural design emphasizing low computational time and easy operation. A material model is developed here, from which the equivalent engineering constants of plies with various angles can be obtained. Based on the material model, a 2D FE model is built to determine distributions of the shear and peel strain in a single-lap adhesively bonded joint. The strain distribution results from the 2D FE model agree well with experimental results, validating the accuracy of the material model. In addition, 2D FE modelling of the non-planar composite π joint under tensile loading is developed by combining the proposed material model and progressive damage method. The damage behavior and ultimate failure load are predicted and good agreements present between the numerical and experimental results. Totally, the reduced computational method combining the 2D FE model and progressive damage method is efficient and simple, can provide an accurate simulation of the damage behavior of complex composite bonded structures and has good prospects for engineering applications. Highlights: A material model is developed, from which the equivalent engineering constants of plies with various angles can be obtained. The accuracy of the material model is validated by comparing the distributions of the shear and peel strain in the adhesive layer of a single-lap adhesively bonded joint against those obtained from experiments. A 2D FE modelling framework of non-planar composite π joint under tensile loading is developed by combining the proposed material model and the progressive damage method. The damage behavior, ultimate failure load and displacement of the non-planar composite π joint are predicted and good agreements are achieved between the numerical and experimental results.